1998
DOI: 10.1126/science.281.5383.1671
|View full text |Cite
|
Sign up to set email alerts
|

A Mammalian Scaffold Complex That Selectively Mediates MAP Kinase Activation

Abstract: The c-Jun NH2-terminal kinase (JNK) group of mitogen-activated protein (MAP) kinases is activated by the exposure of cells to multiple forms of stress. A putative scaffold protein was identified that interacts with multiple components of the JNK signaling pathway, including the mixed-lineage group of MAP kinase kinase kinases (MLK), the MAP kinase kinase MKK7, and the MAP kinase JNK. This scaffold protein selectively enhanced JNK activation by the MLK signaling pathway. These data establish that a mammalian sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
534
2
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 621 publications
(556 citation statements)
references
References 22 publications
19
534
2
1
Order By: Relevance
“…In this study, the activity of RhoA is in part regulated by the enhanced p190RhoGEF expression after CD40 ligation. However, a recent study on neuronal cells also showed that p190RhoGEF can directly bind to the c-Jun N-terminal kinase (JNK)-interacting protein, JIP-1 (13), which is reported to serve as a substrate for JNK (19) and as a scaffolding protein for JNK activation (20). Therefore, further study will be required to determine the possibility that p190RhoGEF may control a wider range of cellular processes than those that are predicted by its GDP/GTP exchange activity.…”
Section: Overexpression Of P190rhogef Enhances the Nf-b Activationmentioning
confidence: 99%
“…In this study, the activity of RhoA is in part regulated by the enhanced p190RhoGEF expression after CD40 ligation. However, a recent study on neuronal cells also showed that p190RhoGEF can directly bind to the c-Jun N-terminal kinase (JNK)-interacting protein, JIP-1 (13), which is reported to serve as a substrate for JNK (19) and as a scaffolding protein for JNK activation (20). Therefore, further study will be required to determine the possibility that p190RhoGEF may control a wider range of cellular processes than those that are predicted by its GDP/GTP exchange activity.…”
Section: Overexpression Of P190rhogef Enhances the Nf-b Activationmentioning
confidence: 99%
“…When overexpressed in mammalian cells, MLK3 activates JNK via the phosphorylation and activation of SEK/MKK4 (Rana et al, 1996) or MKK7 (Whitmarsh et al, 1998). Moreover, putative scaffold proteins, JIP-1 (JNK interacting protein-1) and JIP-2 have recently been identified and shown to interact in a specific manner with members of the MLK family and with MKK7 and JNK, but not with Cdc42, thereby linking these kinase-signaling components (Dickens et al, 1997;Whitmarsh et al, 1998;Yasuda et al, 1999). MLK3 has also been shown to activate the MAPK p38 kinase pathway via MKK3/6 (Tibbles et al, 1996) and the extracellular signal-related protein kinase (ERK) pathway (Hartkamp et al, 1999).…”
Section: Abstract: Apoptosis; Cdc42; Mlk3; Signal Transduction; Sympmentioning
confidence: 99%
“…No proteins providing these associations have been identified, and no information exists about interactions of the nuclear envelope membranes and the cytoskeleton in plants. Compartmentalization of molecular events is the emerging theme in many research areas both for nuclear events, such as replication or transcription (Wei et al, 1998), and, more recently, for cytoplasmic events, such as mitogenactivated kinase pathways (Whitmarsh et al, 1998). In contrast, our knowledge about the cellular structures possibly providing such a compartmentalization and about their dynamic interactions is still in its infancy.…”
Section: Mfp1 and The Mab6c6 Antigen Define A Connection Between The mentioning
confidence: 99%